PENDIDIKAN INTEGRATIF–INTERKONEKTIF; KAJIAN FILSAFAT PENDIDIKAN: Upaya Menemukan Landasan Pendidikan Integratif) - Zulia A’limatun Nisa, Anis (CV. Amerta Media, 2017)
The current social reality, the educational process that takes place in public education institutions and in Islamic educational institutions still separates the two subjects, namely general subjects and religious lessons. Teachers only provide general knowledge during general lessonssuch as IPA, IPS, Indonesian, and others that are general, and vice versa teachers only provide religious knowledge of religious lessons in progress. This suggests that current education still contains dichotomic views. The concept of the integrity of science that is in accordance with the Qur'an and Hadith as well as the scholars' earlier needs to be re-realized in the present era. So it is necessary to study deeply to find the basis of integrative education through philosophical study. It is an attempt to eliminate the existence of a scientific dichotomy or attempt to integrate general science